Dukungan Sosial Sebagai Pendorong Prestasi Anak Keluarga Pemulung Di Ciputat - Femi Putri Yuniar; Moh. Amin Tohari (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Children from scavenger families generally have relatively low education, some children even receive no education at all because the children of scavenger families come from families with a low social and economic life so they are unable to provide education to their children. In this case, it turns out that there are children who can survive and set a good example even though they live in a scavenger's stall with all their limitations, namely children who excel. This research aims to determine social support for children from scavenger families who excel. This research uses descriptive qualitative research. Data collection was carried out by observation, interviews and documentation. Determining informants using purposive sampling. The results of this research are emotional support in the form of attention, care and affection, appreciation support such as receiving praise and recognition of achievements, instrumental support in the form of meeting school equipment needs, information support for help when learning is difficult and social support in the form of being involved in group activities. Supporting factors are due to the desire of children who excel to continue school and inhibiting factors arise from the nature of the children and limited time to meet to provide support.